The Representation of Muslim Women as The Other in The Submission Novel - Pamungkas, Setyari (Universitas Sebelas Maret, 2023)
This research is written based on the analysis of a 9/11 fiction, The Submission by Amy Waldman. This research examines the representation of Muslim women characters in the novel. It is a descriptive qualitative research. The main data consist of words, phrases, sentences, expressions, dialogues, plot, and narrations in the novel. The supporting data are taken from books, e-books, journals, articles, websites and other related references. It is conducted under American studies perspective. It applies some perspectives especially theory of Orientalism to scrutinize the construction of Muslim women in the novel. It also attempts to identify some constructions which differ from the reality of Muslim women generally and American Muslim women as described in other texts. The findings shows that The Submission perpetuates old Orientalism in 21st fiction era which represents Muslim women as the Other. They are represented as sensual, libidinous, devilish, subordinate, oppressed, exotic, and requisite the West assistance.